2015
DOI: 10.1177/0961203314567750
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CXCR5+CD4+helper T cells in systemic lupus erythematosus patients share phenotypic properties with germinal center follicular helper T cells and promote antibody production

Abstract: The accumulated circulating Tfh-like cells in lupus patients share phenotypic and functional properties with GC-Tfh cells. Tfh-like cells may serve as perpetuators in the pathogenesis of SLE by enhancing the self-reactive B cell clones to further differentiate into auto antibody-producing plasmablasts, and ultimately cause autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 42 publications
8
84
0
Order By: Relevance
“…This pattern was associated with greater CD4 Tfh cell numbers, sustained autoantibody production and severe lupus nephritis. These results are consistent with reports that Tfh cells are increased in lupus (48) and that strong T cell stimulation is needed for Th1 differentiation but is not needed for Tfh cell differentiation (49). Differential immune skewing of donor T cells was not secondary to host NK cell function.…”
Section: Discussionsupporting
confidence: 93%
“…This pattern was associated with greater CD4 Tfh cell numbers, sustained autoantibody production and severe lupus nephritis. These results are consistent with reports that Tfh cells are increased in lupus (48) and that strong T cell stimulation is needed for Th1 differentiation but is not needed for Tfh cell differentiation (49). Differential immune skewing of donor T cells was not secondary to host NK cell function.…”
Section: Discussionsupporting
confidence: 93%
“…Leptin is closely related to adipokines, which are associated with oxidative stress and are reported to be overproduced in SLE patients [39, 40]. Previous data indicate that leptin signaling modulates T cell proliferation and preferential differentiation of Th1 cells over Th2 cells [4143].…”
Section: Oxidative Stress and Treg Cellsmentioning
confidence: 99%
“…A previous study found that patients who had received a propofol infusion had a higher percentage of T helper cells,12 but the physiological significance of this has not been elucidated. Recently, researchers found a new type of cells called circulating T helper-like follicular cells in the blood of SLE patients 13. These cells shared similar phenotypic properties with germinal centre follicular helper T cells which could drive B cells to differentiate into IgG secreting plasma cells.…”
Section: Discussionmentioning
confidence: 99%